The Urgency of Updating Buton Regency’s RTRW to Support Sustainable Tourism Development - Samsul Samsul; Eko Satria; L.M. Ricard Zeldi Putra; Muhammad Rahmatul; Muhamad Suntjungi (Dialogia Iuridica)
Buton Regency possesses substantial tourism potential, encompassing natural, cultural, historical, and maritime attractions. However, the sector's contribution to the local economy remains limited due to misalignment between the Regional Spatial Plan (RTRW) and the Regional Tourism Development Master Plan (RIPPDA). This study aims to evaluate the alignment between the RTRW of Buton Regency (2013–2033) and the RIPPDA (2021–2026), and to propose strategic legal policy updates to support superior and sustainable tourism development. This is a normative legal research employing statutory and conceptual approaches. Data were obtained from regional legal documents, policy reports, and other secondary sources. The data were analyzed qualitatively using content analysis to assess the compatibility of legal norms and their impact on tourism development. The findings reveal significant inconsistencies between the RTRW and RIPPDA, particularly in tourism zoning and functional area designations. Such disharmony hampers tourism infrastructure development, reduces legal certainty, and poses risks to environmental sustainability. Proposed strategies include harmonizing RTRW norms with RIPPDA directives, conducting periodic reviews of the spatial plan, and integrating tourism needs into spatial planning frameworks. These efforts are expected to support the development of competitive and sustainable tourism destinations, contributing to economic growth in Buton Regency.